Discovery of two gravitationally lensed quasars in the Dark Energy Survey - Agnello, Adriano (2015)
We present spectroscopic confirmation of two new gravitationally lensed quasars, discovered in the Dark Energy Survey (DES) and Wide-field Infrared Survey Explorer (WISE) based on their multiband photometry and extended morphology in DES images. Images of DES J0115−5244 show a red galaxy with two blue point sources at either side, which are images of the same quasar at zs = 1.64 as obtained by our long-slit spectroscopic data. The Einstein radius estimated from the DES images is 0.51 arcsec. DES J2146−0047 is in the area of overlap between DES and the Sloan Digital Sky Survey (SDSS). Two blue components are visible in the DES and SDSS images. The SDSS fibre spectrum shows a quasar component at zs = 2.38 and absorption by Mg II and Fe II at zl = 0.799, which we tentatively associate with the foreground lens galaxy. Our long-slit spectra show that the blue components are resolved images of the same quasar. The Einstein radius is 0.68 arcsec, corresponding to an enclosed mass of 1.6 × 1011M . Three other candidates were observed and rejected, two being low-redshift pairs of starburst galaxies, and one being a quasar behind a blue star. These first confirmation results provide an important empirical validation of the data mining and model-based selection that is being applied to the entire DES data set.